Loss of Rab6a in the small intestine causes lipid accumulation and epithelial cell death from lactation. Issue 7 (4th June 2020) - Iwaki, Ayano; Moriwaki, Kenta; Sobajima, Tomoaki; Taniguchi, Manabu; Yoshimura, Shin‐ichiro; Kunii, Masataka; Kanda, Satoshi; Kamada, Yoshihiro; Miyoshi, Eiji; Harada, Akihiro
Abstract: Intestinal epithelial cells (IECs) are not only responsible for the digestion and absorption of dietary substrates but also function as a first line of host defense against commensal and pathogenic luminal bacteria. Disruption of the epithelial layer causes malnutrition and enteritis. Rab6 is a small GTPase localized to the Golgi, where it regulates anterograde and retrograde transport by interacting with various effector proteins. Here, we generated mice with IEC‐specific deletion of Rab6a ( Rab6a ∆IEC mice). While Rab6a ΔIEC mice were born at the Mendelian ratio, they started to show IEC death, inflammation, and bleeding in the small intestine shortly after birth, and these changes culminated in early postnatal death. We further found massive lipid accumulation in the IECs of Rab6a ∆IEC neonates. In contrast to Rab6a ∆IEC neonates, knockout embryos did not show any of these abnormalities. Lipid accumulation and IEC death became evident when Rab6a ∆IEC embryos were nursed by a foster mother, suggesting that dietary milk‐derived lipids accumulated in Rab6a‐deficient IECs and triggered IEC death. These results indicate that Rab6a plays a crucial role in regulating the lipid transport and maintaining tissue integrity.